+0  
 
0
192
3
avatar

x^3+x^2+2x+2 factor by grouping so it ends up with two binomials.

Guest Dec 5, 2014

Best Answer 

 #2
avatar+18827 
+5

x^3+x^2+2x+2 factor by grouping so it ends up with two binomials.

$$\small{
\text{Formula:}
$
\boxed{a+ax+x^2+x^3 = (1+x)(a+x^2)}
\\\\
$
\text{Example: }
$\\$
a=2 \qquad 2+2x+x^2+x^3 = (1+x)(2+x^2) \\
a=1 \qquad 1+1x+x^2+x^3 = (1+x)(1+x^2)
$
}$$

heureka  Dec 5, 2014
Sort: 

3+0 Answers

 #1
avatar
+5

You have to play around with it a bit (or a lot) using trial-and-error trying different possibilities until it works.

 

Check your answer here: http://m.wolframalpha.com/input/?i=factorize+x%5E3%2Bx%5E2%2B2x%2B2&x=0&y=0

 

Guest Dec 5, 2014
 #2
avatar+18827 
+5
Best Answer

x^3+x^2+2x+2 factor by grouping so it ends up with two binomials.

$$\small{
\text{Formula:}
$
\boxed{a+ax+x^2+x^3 = (1+x)(a+x^2)}
\\\\
$
\text{Example: }
$\\$
a=2 \qquad 2+2x+x^2+x^3 = (1+x)(2+x^2) \\
a=1 \qquad 1+1x+x^2+x^3 = (1+x)(1+x^2)
$
}$$

heureka  Dec 5, 2014
 #3
avatar+91435 
0

This factorization could be handy to remember.  Thanks Heureka.

Melody  Dec 5, 2014

25 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details